2003
DOI: 10.1074/jbc.m211286200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism of the Co-regulation of Nuclear Transport of SmgGDS and Rac1

Abstract: The armadillo protein SmgGDS promotes guanine nucleotide exchange by small GTPases containing a C-terminal polybasic region (PBR), such as Rac1 and RhoA. Because the PBR resembles a nuclear localization signal (NLS) sequence, we investigated the nuclear transport of SmgGDS with Rac1 or RhoA. We show that the Rac1 PBR has significant NLS activity when it is fused to green fluorescent protein (GFP) or in the context of full-length Rac1. In contrast, the RhoA PBR has very poor NLS activity when it is fused to GFP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
131
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(144 citation statements)
references
References 37 publications
11
131
2
Order By: Relevance
“…However, a recent report challenges this view, demonstrating the presence of Rac1 in the nuclear compartment of cells (Lanning et al, 2003). Our data support the nuclear localization of Rac1.…”
Section: Pbr Region Of Rac1 Important For Mediating B-catenin/ Tcf Tasupporting
confidence: 70%
See 2 more Smart Citations
“…However, a recent report challenges this view, demonstrating the presence of Rac1 in the nuclear compartment of cells (Lanning et al, 2003). Our data support the nuclear localization of Rac1.…”
Section: Pbr Region Of Rac1 Important For Mediating B-catenin/ Tcf Tasupporting
confidence: 70%
“…Rac1 was recently identified to have a functional nuclear localization signal sequence present at the Cterminus denoted the polybasic region (PBR), found to enhance the nuclear accumulation of protein complexes containing SmgGDS and Rac1 (Lanning et al, 2003). Nuclear expression of V12Rac1PBRQ mutant was significantly decreased in HCT116 cells (Figure 6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Localization of Rac1 to the membrane and cytoplasm is important for Rac1 activity and function in promoting lamellipodia formation [75][76][77]. Nuclear accumulation of Rac1 has been shown to affect stability of Rac1 and eventually lead to Rac1 protein degradation [77,82,83]. Both the disruption of lamellipodia and localization of Rac1 to the nucleus in P19 cells expressing miR-124 suggest that miR-124 may indirectly downregulate the activity of Rac1 in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…A careful examination of RhoGDIa amino acid sequence failed to identify any nuclear localization signal, suggesting that another protein may assist in the shuttling of RhoGDIa between the cytoplasm and the nucleus. It seems plausible that cdc42 isoform1, a RhoGTPase family member with a polybasic region in its C-terminal end that can function as a nuclear localization signal (Lanning et al 2003, Williams 2003, might perform this function since we identified both isoforms 1 and 2 of cdc42 in our agarose gel purification experiments as ERa-associated proteins (Schultz-Norton et al 2007). Alternatively, RhoGDIa could be accompanied by a protein such as 14-3-3, which binds and helps to redistribute an array of signaling proteins (Fu et al 2000, Kino et al 2003, Diviani et al 2004.…”
Section: Discussionmentioning
confidence: 99%